Screening of Penaeus vannamei Boone, 1931 collected from east coast of India for monodon baculovirus (MBV) and hepatopancreatic parvovirus (HPV) - Jagadeesan, V.; Ezhil Praveena, P.; Bhuvaneswari, T.; Jithendran, K. P.; Otta, S. K. (Indian Journal of Fisheries, 2018)
Aquaculture is one of the fastest growing sectors yielding more than 10% growth rate per annum over the past 10 years, with a contribution of about 16% of animal protein production globally. Aquaculture production has surpassed that of the other meat producing sectors. Diseases, especially of viral etiology, remains a stumbling block for the growth of this sector posing great threat. The major viruses affecting shrimps in India are white spot syndrome virus (WSSV) and infectious hypodermal hematopoietic necrosis virus (IHHNV). Besides this, monodon baculovirus (MBV) and hepatopancreatic parvovirus (HPV) also cause considerable loss to the shrimp farmers. MBV outbreaks can cause mass mortalities when combined with other viral diseases. Moreover, MBV and HPV infections can lead to slow growth in cultured penaeid shrimps, thereby affecting the production. Although studies pertaining to the prevalence of these two viruses in the tiger shrimp Penaeus monodon have been reported extensively, similar information on Penaeus vannamei farming is scanty. Hence a pilot study was undertaken to screen P. vannamei samples collected from various farms of Tamil Nadu, Andhra Pradesh and West Bengal. Shrimp samples (n=20) from six farms during 35-75 days of culture (DOC) were collected for screening by PCR. It was found that all the samples were negative for MBV and HPV. It could be concluded that the prevalence of both these viruses in P. vannamei are either absent or very low.